Protocol for a Field Trial of a Hearing and Vision Support Intervention for People Living in Long‐Term Care in Australia - Carly Meyer; Najwan El‐Saifi; Naomi Rose; Kasia Bail; Colette Browning; Dayna Cenin; Antonio Ahumada‐Canale; Megan Campbell; Tim England; Melanie Ferguson; Yuanyuan Gu; Reema Harrison; et al. (Health Expectations)
ABSTRACT Introduction Hearing and vision impairments are prevalent among residents in long‐term care settings. Hearing and vision impairments frequently go unsupported, affecting residents' quality of life and healthcare costs. This paper describes the protocol for a pre−post evaluation and process evaluation of a pragmatic sensory support intervention (SSI) that was developed with residents, informal caregivers and long‐term care workers. Methods and Analysis A prospective pre−post‐intervention trial within long‐term care will be conducted, including three groups: residents (n = 87), informal caregivers (n = 87) and long‐term care workers (n = 40). Outcome measures include health‐related quality of life and well‐being measures relevant to each group measured at baseline, 3‐ and 6‐months post‐intervention. Health resource and sensory device utilisation will be captured from routine data and by direct observation. Qualitative interviews, including a representative sample of residents and informal caregivers, will be conducted as part of a simultaneous process evaluation. Generalised linear models and paired t‐tests will be used to evaluate the effects on residents' and caregivers' quality of life and sensory device use. The cost‐effectiveness of the intervention will be examined using within‐trial analysis, economic modelling and budget impact assessment. A process evaluation will use descriptive statistics and thematic analysis to assess the intervention's reach, adoption, implementation, acceptability, mechanisms of change and contextual influences. Conclusion Hearing and vision impairments are common but under‐supported in older adults in long‐term care. This protocol involves a systematic evaluation of the effectiveness and implementation challenges of a pragmatic SSI to optimise hearing and vision function and improve the quality of life for long‐term care residents and their caregivers.